AN INTEGRATED APPROACH BASED ON A BI-LEVEL GENETIC ALGORITHM AND A COMBINED ZONE- LP FOR THE FACILITY LAYOUT PROBLEM - Mohamadi, Arash; Ebrahimnejad, Sadalah; Soltani, Roya; Khalilzadeh, Mohammad (The South African Journal of Industrial Engineering, 2019)
In this study, a new integrated approach is presented to solve the facility layout problem with unequal areas in an open field. This approach includes a two-stage method and a bi-level genetic algorithm. In the first stage of the proposed method, the arrangement of departments adjacent to each other is determined by an improved zone algorithm; in the second stage, the layout obtained from the first stage is improved by using a linear programming model, and the final locations of the departments are thus determined. This two-stage method is used in a bi-level genetic algorithm to achieve an appropriate layout. The orientation and aspect ratios of the departments are determined at the first level of the algorithm, and at the second level, the sequence of the departments is determined for the layout. The proposed approach is compared with the four approaches in the literature, by using 10 datasets in order to evaluate efficiency and performance. The quality of the proposed approach is confirmed by improving the best solutions obtained from previous studies in seven datasets. Furthermore, the presented approach obtains the best solutions from previous studies in the other three datasets.